The Influence of Marketing Communication and Trust on Customer Loyalty with Customer Satisfaction as an Intervening Variable at PT. Media Synergy in 2023 - Belinda, Belinda; Subagyo, Ahmad (Universitas Indraprasta PGRI, 2023)
This research aims to see the influence of marketing communications, and trust on customer loyalty through customer satisfaction. This study was conducted at PT. Medial Synergy. This research uses a quantitative approach by applying a purposive sampling technique in selecting male and female samples and using the Konigsee Implant five times in one month. A total of 50 questionnaires were distributed to respondents. The analysis method used in this research is by using path analysis and assisted by the SPSS analysis application. Research findings show that marketing communication has a positive but not significant effect on customer loyalty, Apart from that trust has a significant positive effect on customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty, then marketing communication has a significant positive effect on customer satisfaction, there is a positive effect and significant trust in customer satisfaction, the indirect effect shows that customer satisfaction cannot mediate between marketing communications and customer loyalty, while customer satisfaction is proven to be able to mediate between trust and customer loyalty.